Microbiota Profile and Impact of Fusobacterium nucleatum in Colorectal Cancer Patients of Barretos Cancer Hospital - de Carvalho, Ana Carolina; de Mattos Pereira, Leandro; Datorre, José Guilherme; dos Santos, Wellington; Berardinelli, Gustavo Noriz; Matsushita, Marcus de Medeiros; Oliveira, Marco Antonio; Durães, Ronilson Oliveira; Guimarães, Denise Peixoto; Reis, Rui Manuel (Frontiers in Oncology, 2019)
Microbial diversity has been pointed as a major factor in the development and progression of colorectal cancer (CRC). We sought to explore the richness and abundance of the microbial community of a series of colorectal tumor samples treated at Barretos Cancer Hospital, Brazil, through 16S rRNA sequencing. The presence and the impact of Fusobacterium nucleatum (Fn) DNA in CRC prognosis was further evaluated by qPCR in a series of 152 colorectal cancer cases. An enrichment for potentially oncogenic bacteria in CRC was observed, with Fusobacterium being the most abundant genus in the tumor tissue. In the validation dataset, Fn was detected in 35/152 (23.0%) of fresh-frozen tumor samples and in 6/57 (10.5%) of paired normal adjacent tissue, with higher levels in the tumor (p=0.0033). Fn DNA in the tumor tissue was significantly associated with proximal tumors(p=0.001), higher depth of invasion (p=0.014), higher clinical stages (p=0.033), poor-differentiation (p=0.011), MSI-positive status (p<0.0001), BRAF mutated tumors (p<0.0001), and with the loss of expression of mismatch-repair proteins MLH1 (p<0.0001), MSH2 (p=0.003) and PMS2 (p<0.0001). Moreover, the presence of Fn DNA in CRC tissue was also associated with a worse patient cancer-specific survival (69.9% versus 82.2% in 5 years; p=0.028) and overall survival (63.5% versus 76.5%; p=0.037). Here we report, for the first time, the association of F. nucleatum presence with important clinical and molecular features in a Brazilian cohort of CRC patients. Tumor detection and classification based on the gut microbiome might provide a promising approach to improve the prediction of patient outcome.